Heterogeneity and Function of Kupffer Cells in Liver Injury - Li, Weiyang; Chang, Na; Li, Liying (Frontiers in Immunology, 2022)
Kupffer cells (KCs) are key regulators of liver immunity composing the principal part of hepatic macrophages even body tissue macrophages. They reside in liver sinusoids towards portal vein. The micro-environment shapes KCs unique immunosuppressive features and functions. KCs express specific surface markers that distinguish from other liver macrophages. By engulfing gut-derived foreign products and apoptotic cells without triggering excessive inflammation, KCs maintain homeostasis of liver and body. Heterogeneity of KCs has been identified in different studies. In terms of the origin, adult KCs are derived from progenitors of both embryo and adult bone marrow. Embryo-derived KCs compose the majority of KCs in healthy and maintain by self-renewal. Bone marrow monocytes replenish massively when embryo-derived KC proliferation are impaired. The phenotype of KCs is also beyond the traditional dogma of M1-M2. Functionally, KCs play central roles in pathogenesis of acute and chronic liver injury. They contribute to each pathological stage of liver disease. By initiating inflammation, regulating fibrosis, cirrhosis and tumor cell proliferation, KCs contribute to the resolution of liver injury and restoration of tissue architecture. The underlying mechanism varied by damage factors and pathology. Understanding the characteristics and functions of KCs may provide opportunities for the therapy of liver injury. Herein, we attempt to afford insights on heterogeneity and functions of KCs in liver injury using the existing findings.